OC-025 Endoclot polysaccharide haemostatic system to reduce delayed bleeding following upper and lower gastrointestinal resection – preliminary results of the haemostop study. (22nd June 2015) - Chedgy, FJQ; Bhattacharyya, R; Kandiah, K; Kumar, A; Bhandari, P
Abstract : Introduction: Endoscopic resection of advanced neoplasia in the upper and lower gastrointestinal tract is now possible with the techniques of endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR). However, these techniques create large mucosal defects, subsequently increasing the risk of significant post-procedural bleeding with catastrophic consequences. Endoclot TM is a topical hemostatic powder that rapidly absorbs water creating a high concentration of platelets, red blood cells and clotting factors – accelerating the natural coagulation cascade. Routine application of Endoclot TM to ESD or EMR defects is hypothesised to reduce the risk of significant post EMR/ESD bleeding. Method: Prophylactic use of Endoclot TM, following endoscopic resection of large lesions, to prevent delayed bleeding was introduced in June 2014. Results: Group A (pre-Endoclot TM era): 496 patients, with polyps >20 mm, underwent lower gastrointestinal EMR/ESD at our institution between 2005 and 2013 with a mean polyp size of 43 mm and 12% with scarring. Significant delayed bleeding was seen in 21 of 496 patients (4%). 264 patients underwent upper gastrointestinal EMR/ESD at our institution between 2005 and 2013. Significant delayed bleeding was seen in 9 of 264 patients (3%). Group B (Endoclot TM group): All patients undergoing endoscopic resection since June 2014 have had Endoclot TM sprayed onto the resection base. To date, 37 patients have undergone colonic EMR/ESD (mean polyp size 42 mm, 43% scarred) and 30 patients have undergone upper gastrointestinal resection. There was 1 significant delayed bleed in the colonic group (3%) requiring further endoscopic therapy. This patient had inadequate coverage (30%) of Endoclot TM due to device clogging, experienced early in the use of Endoclot TM . There were 2 (7%) bleeds in the upper GI group, which were managed with further endoscopic therapy without the need for blood transfusion. There have been no complications related to Endoclot TM use. Conclusion: Endoclot TM shows promise in reducing the risks of delayed bleeding following endoscopic resection of neoplastic lesions from the gastrointestinal tract. Although our study group is small, we have demonstrated a 1% reduction in risk of delayed bleeding following EMR/ESD for large colonic polyps in a group with a significantly higher rate of scarring and therefore bleeding risk. A randomised controlled trial is required to clarify the role of routine use of Endoclot TM following EMR/ESD. Disclosure of interest: None Declared.